2017
DOI: 10.1061/(asce)em.1943-7889.0001247
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study on the Dynamic Properties of Viscoelastically Coupled Shear Walls in High-Rise Buildings

Abstract: An innovative method of using viscoelastic (VE) dampers as coupling members between reinforced concrete shear walls has been recently developed for enhancing the wind performance and seismic resilience of tall buildings. Although three-dimensional finite-element models are used for the final design of such systems, fundamental analytical models that can be used to gain broader insights into their dynamic response have not yet been developed. Therefore, in this paper a sixth-order partial differential equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…3,4 Christopoulos et al [5][6][7] developed a viscous coupling damper (VCD) with a replaceable shear-critical structural fuse to accommodate the short span of the coupling beams. Nonlinear dynamic analysis indicated that fewer coupling beams were damaged or required repair due to the installation of VCDs, 5 and analytical models of the VCDs 8 as well as the tall shear walls with VCDs were proposed and verified. 9 Kim et al 10 proposed a new type of hybrid energy-dissipation coupling beam that consisted of U-shaped steel plates and high damping rubbers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Christopoulos et al [5][6][7] developed a viscous coupling damper (VCD) with a replaceable shear-critical structural fuse to accommodate the short span of the coupling beams. Nonlinear dynamic analysis indicated that fewer coupling beams were damaged or required repair due to the installation of VCDs, 5 and analytical models of the VCDs 8 as well as the tall shear walls with VCDs were proposed and verified. 9 Kim et al 10 proposed a new type of hybrid energy-dissipation coupling beam that consisted of U-shaped steel plates and high damping rubbers.…”
mentioning
confidence: 99%
“…Nonlinear dynamic analysis indicated that fewer coupling beams were damaged or required repair due to the installation of VCDs, 5 and analytical models of the VCDs 8 as well as the tall shear walls with VCDs were proposed and verified. 9 Kim et al 10 proposed a new type of hybrid energy-dissipation coupling beam that consisted of U-shaped steel plates and high damping rubbers. The improved seismic performance of the shear wall with the new type of coupling beam was verified via a static cyclic loading test 10 and shaking table test.…”
mentioning
confidence: 99%
“…The CB was found to exhibit excellent chord rotation and energy dissipation capacity. The seismic response of the overall structure with replaceable CB was also studied and found to be significantly enhanced (Lv et al, 2018;Pant et al, 2017), verifying the feasibility of the design concept, assuming that the permanent set of the damaged structure can be resumed.…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, FNAs and direct-integration RHAs were used in this study, which are accurate methods of carrying out such analysis for buildings with linear damping devices such as VCDs. Alternatively, complex modal analysis-based methods that are not available in ETABS and Perform-3D but can be implemented using other computer programs can also be used Xu 1999, 2000;Pant et al 2017a).…”
Section: Wind Testsmentioning
confidence: 99%